2000
DOI: 10.1007/s12144-000-1007-7
|View full text |Cite
|
Sign up to set email alerts
|

Commitment to one’s spouse as a predictor of marital quality among older couples

Abstract: The present study examined the relationships between several independent variables (ego development, commitment to the spouse, length of marriage, church attendance, and sex of subject) and three marital quality variables (marriage problems, expression of love, and dyadic adjustment) in a community sample of 72 married couples age 50 and up. Commitment to the spouse was the strongest and most consistent predictor of marital quality; commitment was negatively related to marriage problems and positively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
1
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 27 publications
6
11
1
3
Order By: Relevance
“…Gender differences have been found in the household division of labour, parenting styles and responsibilities, the expression of sexual intimacy and in psychological orientation (Heaton and Blake, 1999 McRae and Brody (1989) found that being in a happy marriage is more important to women than men. Haynes et al (1992) compared men and women on eight different aspects of marital satisfaction and found that men reported significantly higher satisfaction than did women on four of the eight comparisons (the other four comparisons did not yield statistically significant sex differences) (Clements and Swensen, 2000). In contrast, Gilford and Bengtson (1979) and Levenson et al (1993) found no gender differences with regard to marital satisfaction (Clements and Swensen, 2000) which is consistent to finding of the present study.…”
Section: Gender and Marital Satisfactionsupporting
confidence: 87%
See 1 more Smart Citation
“…Gender differences have been found in the household division of labour, parenting styles and responsibilities, the expression of sexual intimacy and in psychological orientation (Heaton and Blake, 1999 McRae and Brody (1989) found that being in a happy marriage is more important to women than men. Haynes et al (1992) compared men and women on eight different aspects of marital satisfaction and found that men reported significantly higher satisfaction than did women on four of the eight comparisons (the other four comparisons did not yield statistically significant sex differences) (Clements and Swensen, 2000). In contrast, Gilford and Bengtson (1979) and Levenson et al (1993) found no gender differences with regard to marital satisfaction (Clements and Swensen, 2000) which is consistent to finding of the present study.…”
Section: Gender and Marital Satisfactionsupporting
confidence: 87%
“…Haynes et al (1992) compared men and women on eight different aspects of marital satisfaction and found that men reported significantly higher satisfaction than did women on four of the eight comparisons (the other four comparisons did not yield statistically significant sex differences) (Clements and Swensen, 2000). In contrast, Gilford and Bengtson (1979) and Levenson et al (1993) found no gender differences with regard to marital satisfaction (Clements and Swensen, 2000) which is consistent to finding of the present study.…”
Section: Gender and Marital Satisfactionsupporting
confidence: 87%
“…The therapy could use these resources to strength the bond avoiding the interventions that threaten those beliefs. Other studies have confirmed that shared values provide an important source of support for satisfied long-term couples (Clements & Swensen, 2000;Kaslow & Robison, 1996;Lauer & Lauer, 1986;Roizblatt et al, 1999).…”
Section: Differences In Factors Preventing Gridlock Situations By Difmentioning
confidence: 89%
“…Research has demonstrated that commitment, which could be defined as the feeling of psychological attachment toward a relationship, is a central factor in predicting important relationship outcomes, including marital quality (Clements & Swensen, 2000), better communication (Stanley, 2005), and long-term stability (Fenell, 1993). Commitment also serves as a mediator between stay/leave decisions in romantic relationships (Drigotas & Bart, 2001;Rusbult, 1983).…”
Section: Commitment As a Predictor Of Infidelitymentioning
confidence: 99%